The Effects of Peer Attachment on Deliquent Behavior (A Meta-analysis Study) - Yuliandari, Elly; Sugiyanto (ANIMA Indonesian Psychological Journal, 2011)
This meta-analytic study was conducted through an analysis of 13 studies correlating peer at- tachment to delinquency. Subjects (N = 9823) were respondents aged 10 to 18 years. Result shows a positive and significant correlation between delinquency and peer attachment (rho = .4834 on a 95% degrees of significance and interval of standard deviation = .02787). This study supports previous studies, which reveal correlation between peer attachment and delin- quency. Penelitian dengan menggunakan metaanalisis ini dilakukan dengan analisis terhadap 20 studi yang mengaitkan kelekatan sebaya dan perilaku delinkuen. Subjek penelitian meli- batkan 9823 responden yang berusia antara 10 hingga 18 tahun. Hasil yang diperoleh me- nunjukkan adanya korelasi positif dan signifikan antara kenakalan dan kelekatan sebaya (rho = .4834; dengan taraf kepercayaan 95% dan interval SD = .02787). Penelitian ini mendukung hasil penelitian sebelumnya yang mengungkapkan hubungan antara kelekatan sebaya dan kenakalan.